CircTRNC18 inhibits trophoblast cell migration and epithelial–mesenchymal transition by regulating miR-762/Grhl2 pathway in pre-eclampsia. Issue 11 (2nd November 2019) - Shen, Xue-Yan; Zheng, Li-Li; Huang, Jing; Kong, Hong-Fang; Chang, Ya-Jing; Wang, Fang; Xin, Hong
ABSTRACT: Dysfunctions of epithelial–mesenchymal transition (EMT)-regulated cell migration and invasion have been involved in the pathogenesis of pre-eclampsia (PE). However, the role of circRNAs in EMT of PE has not been widely investigated. In this study, we identified that circTNRC18 was upregulated in PE placentas compared with normal pregnancy placentas. Moreover, circTNRC18 negatively regulated trophoblast cell migration and EMT. Overexpression of circTNRC18 reduced while depletion of circTNRC18 enhanced trophoblast cell migration and EMT. Mechanistically, circTNRC18 sponged miR-762 contributed to inhibit miR-762 activity and elevated EMT-related transcriptional factor Grhl2 protein level. miR-762 expression was lower in PE placentas and played a promoting role in trophoblast cell migration and EMT. In contrast, Grhl2 was highly expressed in PE placentas. Furthermore, we confirmed that upregulation of Grhl2 by circ-TNRC18-induced inhibition of miR-762 led to trophoblast cell migration and EMT. In conclusions, circTNRC18/miR-762/Grhl2 axis plays a key role in trophoblast cell migration and EMT. circTNRC18/miR-762/Grhl2 axis may be a potential therapeutic target in PE.